2018
DOI: 10.1111/hir.12217
|View full text |Cite
|
Sign up to set email alerts
|

Information literacy skills and training of licensed practical nurses in Alberta, Canada: results of a survey

Abstract: The results suggest there are significant gaps in the preparedness and ability of LPNs to access and apply research evidence effectively in the workplace. There are several areas in which the training provided by Librarians appears either misaligned or ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
2
16
0
5
Order By: Relevance
“…These findings correspond to evidence suggesting that some new LPN graduates, the majority of whom hold two-year diplomas, have not been well prepared to identify, access, and evaluate the most appropriate research for practice [54]. The expectation that LPNs will use research evidence to the same extent as RNs in nursing practice varies across Canadian LPN regulatory groups [10].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These findings correspond to evidence suggesting that some new LPN graduates, the majority of whom hold two-year diplomas, have not been well prepared to identify, access, and evaluate the most appropriate research for practice [54]. The expectation that LPNs will use research evidence to the same extent as RNs in nursing practice varies across Canadian LPN regulatory groups [10].…”
Section: Discussionsupporting
confidence: 63%
“…The top ranking of Internet search engines was similarly found in a study of newly graduated LPNs in one Canadian province [54]. Where rural nurses work alone or with few colleagues [55, 56], an Internet search may be an accessible alternative to consulting a colleague.…”
Section: Discussionmentioning
confidence: 88%
“…On the basis of Wadson's [16] research questionnaire of nurses' information literacy and an extensive review of literature, we translated and adapted the information literacy questionnaire through expert argumentation to make it more suitable for Chinese nurses. Through the pre-experiment, the questionnaire had good reliability and validity.…”
Section: Nurse Information Literacy Questionnairementioning
confidence: 99%
“…Mokhtar et al [15] found that 36.5% of nurses occasionally used medical subject headings for retrieval, and 26.1% of nurses never used them while at least 70% of nurses did not realize that they could use medical subject headings for more e cient retrieval, which greatly restricted the use of information. A survey of Canadian nurses indicated that approximately 25-38% had mastered information literacy skills in their professional practice [16].…”
Section: Introductionmentioning
confidence: 99%
“…Wadson and Phillips’ () article reports on a survey of licensed practical nurses in Canada which sought to identify their information literacy skills and the training and support required to improve these skills. The results suggest there are significant gaps in the preparedness and ability of this group of nurses to access and apply research evidence effectively in the workplace.…”
Section: Evidence‐based Practicementioning
confidence: 99%